Pengaruh Nilai yang Dirasakan Pasien dan Kepuasan Pasien Terhadap Minat Kunjungan Ulang Pasien Non JKN Dengan Mediasi Citra Merek di Departemen Rawat Jalan Rumah Sakit X - Taruna, Dicky; Assa, Adrie Frans (Dinasti Review Publisher, 2025)
This study aims to analyze the influence of perceived patient value and patient satisfaction on the revisit intention of non-National Health Insurance (non-JKN) patients at Hospital X, with brand image as a mediating variable. The research employs a quantitative approach using Structural Equation Modeling (SEM) with SmartPLS. Data were collected from 100 non-JKN patients visiting the outpatient department. The findings indicate that brand image has a positive and significant effect on revisit intention, and patient satisfaction significantly influences brand image. However, neither perceived value nor patient satisfaction has a significant direct effect on revisit intention. Brand image significantly mediates the effect of patient satisfaction on revisit intention, but it does not mediate the effect of perceived value. These findings highlight the importance of developing and maintaining a strong brand image to enhance patient loyalty, especially among non-JKN patients.